2001
DOI: 10.1080/01652176.2001.9695117
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition: Commercial diet induced hypothyroidism due to high iodine. A histological and radiological analysis

Abstract: A number of puppies of the School Hospital of the Faculty of Veterinary Science-UBA showed bone changes. Measurement of the iodine content of the commercial diet showed a significant increase in its content. Iodine excess causes alterations in thyroid function and morphology, and its hormones have a direct action on bone formation. Three groups of puppies were fed on different diets: a home-prepared diet, a commercial diet (containing 5.6 mg potassium iodide/kg dry food), and a home-prepared diet supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…In the dog reported here, the minimal increase in serum phosphorus concentration and unremarkable serum ALP activity detected during the goitrous hypothyroid phase were inappropriate given the young age of the dog and may have indicated that hypothyroidism was retarding growth of the dog. 23 In the dog reported here, the increases in serum ALP activity and serum phosphorus concentration that were detected after thyroid function was restored supported the hypothesis that these were hypothyroid-induced abnormalities. 23 In the dog reported here, the increases in serum ALP activity and serum phosphorus concentration that were detected after thyroid function was restored supported the hypothesis that these were hypothyroid-induced abnormalities.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the dog reported here, the minimal increase in serum phosphorus concentration and unremarkable serum ALP activity detected during the goitrous hypothyroid phase were inappropriate given the young age of the dog and may have indicated that hypothyroidism was retarding growth of the dog. 23 In the dog reported here, the increases in serum ALP activity and serum phosphorus concentration that were detected after thyroid function was restored supported the hypothesis that these were hypothyroid-induced abnormalities. 23 In the dog reported here, the increases in serum ALP activity and serum phosphorus concentration that were detected after thyroid function was restored supported the hypothesis that these were hypothyroid-induced abnormalities.…”
Section: Discussionsupporting
confidence: 80%
“…Most reported cases of goiter in dogs are congenital in origin, [20][21][22] although dietary (iodine-deficient and iodine-excess) 23,24 and drug-induced 6 goiter have also been described. In 2 reports of dogs with congenital goiter, a nonsense mutation in the gene for thyroid peroxidase was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Two histologic changes were observed in the thyroids of dogs with iodine deficiency. Ingestion of diets containing an excessive amount of iodine caused impairment of thyroid function and hypothyroidism in puppies fed a high iodine diet for 45 days (Castillo et al, 2001). Follicular cell hyperplasia was present, and increased uptake and rapid release of radioiodine occurred.…”
Section: Iodine Deficiency/excessmentioning
confidence: 99%
“…Silva et al (1987) descreveram bócio e osteopetrose em fetos e recém-nascidos cujas mães (éguas) ingeriram, junto com o sal, quantidades extremamente elevadas de iodo. Cães jovens que ingerem dietas muito ricas em iodo desenvolvem, dentro de poucos meses, osteopatia metabólica determinada pelo hipotireoidismo (Castillo et al 2001, Castillo 2002.…”
Section: Interação Da Vitamina D Com Os Hormônios Tireoidianosunclassified